RESULTS OF REFORMS BEING IMPLEMENTED IN THE SYSTEM OF MANDATORY ENFORCEMENT - Urazaliev Murod Koraevich (PT. Antis International Publisher, 2025)
Objective: This paper aims to explore the reforms in the enforcement of court and other authorities' documents in Uzbekistan, with a focus on the establishment of the Bureau of Mandatory Enforcement and the introduction of digitalized enforcement procedures to ensure timely and effective execution of judicial decisions. Method: The study examines legal documents, including Presidential Decrees and Resolutions, along with a review of enforcement practices and the role of state enforcers. It also assesses the implementation of simplified procedures and mediation systems in enforcement proceedings. Results: The establishment of the Bureau of Mandatory Enforcement, the introduction of digital enforcement documents, and the implementation of a simplified procedure for certain debts have significantly improved enforcement efficiency. These reforms aim to ensure the full protection of citizens' legal interests while reducing the state's administrative burden. Novelty: The research highlights the innovative steps taken in Uzbekistan's enforcement system, such as the use of information-communication technologies for remote collection and the introduction of a minimum guaranteed income policy to protect citizens from excessive debt recovery.